Building services design management - Portman, Jackie (Wiley-Blackwell, 2014)
Building services engineering design requires technical skills to ensure that the systems are safe, compliant with legislative requirements and good practices and are coordinated with the needs of the other design and construction team professionals. Design management is the business side of design, encompassing the on-going processes, business decisions, and strategies that enable innovation, and create effectively designed systems and services that ultimately enhance the quality of the built environment and should also provide organisational success to those involved.